Utopia in Crisis? Subaltern Imaginations in Contemporary Bihar - Roy, I (Routledge, 2015)
The Subaltern Studies Collective inaugurated an important point of departure in Indian historiography and social sciences by demanding that attention be directed to subalterns (a term adapted from Gramsci’s Prison Notebooks) as makers of their own destinies. Their scholarship raises three issues, which are discussed in this article. The first of these relates to the empirical observation about subaltern resistance to elites. The second pertains to the analytical dichotomy between elite and subaltern modes of conducting politics. The third centres on the valorisation of a putatively coherent fragment that seeks autonomy from the totality of the state. The fundamental problem with the perspective advanced by the subaltern studies scholars stems from their implicit assumption that utopian ideals centred on reclaiming dignity and asserting social equality are necessarily derivative of European Enlightenment ideals.